Exploring Students’ Procedural Knowledge in Determining the Quality of Liquids - M. Agus Martawijaya; Mutahharah Hasyim; Nurul Wahdah; Muhammad Taqwin (Jurnal Pendidikan Fisika, 2023)
The objective of this research is to describe students' procedural knowledge at SMAN 9 Makassar. This research is qualitative research with a descriptive approach. The subjects in this research were XI-grade students of SMAN 9 Makassar who were considered to have good physics mastery. The instruments used in this research are the researchers themselves, with additional instruments in the form of procedural tests and procedural assessment sheets for students. The data were collected from the provision of procedural test instruments with interviews and documentation. The data tested for validity is then analyzed. The results of this research show that the procedural knowledge of students at SMAN 9 Makassar in determining the quality of liquids (cooking oil) is still in the moderate category. There are 50% of respondents who are in the category. This is based on the analysis that has been carried out on the respondents’ answers. Therefore, this study implies that teachers should find more strategies to improve students’ procedural knowledge, particularly in determining liquid quality.